PELATIHAN CAPACITY BUILDING - Yani, Fitri; Putra, Rizaldi; Purnama, Intan; Suharti, Suharti; Aprila, Bord Nandre; Saputra, Hidayat; Rusilawati, Ermina (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2024)
Capacity Building is very important in this era of digital transformation. Capacity Building includes improving the skills, knowledge and capabilities of individuals, organizations and communities in order to adopt and make the most of digital technology. Until now, no coaching activities have been carried out in the form of increasing the capacity and skills of service officer resources. So the Riau Province Regional Revenue Agency (Bapenda) carried out Capacity Building Training activities aimed at Riau Province Bapenda's social security service officers. Through this training participants were taught how to provide excellent service, capacity building, and skilled in communication.